Implementasi Manajemen Keragaman Sumber Daya Manusia - Djadji, Osfred Umbu; Andadari, Roos Kities (Jurnal Samudra Ekonomi dan Bisnis, 2021)
The purpose of this research is to provide an overview of the implementation, forms of implementation and problems encountered in implementing diversity management in relation to human resource management (HRM) practices at SWCU. This qualitative research conducted through case studies. Key persons in this study were four university leaders and one staff member. Data obtained through in-depth interview process and then analyzed in three descriptive techniques. The results showed that the practice of implementing HR management diversity management was carried out well based on performance, fair and there was no discrimination. The implementation problems encountered at SWCU are divided into two parts, namely practice inside and outside the HRM. Practical problems in HRM occur at the training and promotion stages; and, problems that occur outside the HRM practice such as communication problems and different perspectives.